ANALYSIS OF THE DEVELOPMENT OF THREATS TO THE SOCIO-ECONOMIC SYSTEM "CITY" - ROMANOVSKA, Yuliya (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Consideration of a city socio-economic security in borders of a protective approach involves identifying threats to the "city" socio-economic system, studying their nature, sources of occurrence, identifying their character and forecasting the consequences of their implementation. There is a threat to the socio-economic system "city" considered in the paper as processes and phenomena occurring in the external and internal environment of the system, which, in the presence of a certain combination of conditions and circumstances in the system functioning, are capable to make negative changes in a such system. Threats to the socio-economic system "city" do not arise suddenly, immediately and unexpectedly. The threat to the socio-economic system "city" first arises under certain conditions. After the occurrence one can identify such threat, further such threat is allowed to happen. In case of absence of security activity in managing the city, such threat is going to be institutionalized. The gradual nature of implementing threats to the socio-economic system "city" determines the expediency of their study using the "development" category and postulates of the process approach. Recognizing development of the threat to the socio-economic system "city" led to necessity of its analysis, the sequence of which is provided in the article using the concepts of the process approach and taking into account the features of threats as an object of development. An example of the list of threats to the socio-economic system "city" is presented. Their description procedure is described. The proposed procedure of analysis of development of the threat to the socio-economic system "city" according to its stages is shown on the example of development of the threat "Housing stock and city communal infrastructure deterioration" (on the example of communal transport). It is shown that threats to the socio-economic system "city" are multiple, diverse by nature, development dynamics, scale of the consequences, sources. However, development of these threats has certain general regularities, which can be determined by such development analyzing. Identifying such regularities as a result of analyzing the development of threats according to a certain sequence can be used as a framework for the security activities of the city authorities, the purpose of which is to strengthen the socio-economic security of the city.